Myopericarditis in children and adolescent: Is the elevated troponin and chest pain as alarming as we thought? - (:unkn) unknown (Cambridge University Press, 2021)
Aim: When encountering adolescents with chest pain and a high troponin level but with no underlying coronary artery illness, it is advisable to consider myopericarditis. Though myopericarditis is a self-limiting, benign condition, it nevertheless causes anxiety in the patient and the family. Methods: Thirty-nine patients diagnosed with myopericarditis were included. We retrospectively analysed the demographic and clinical features, laboratory tests, echocardiography, electrocardiograms, MRI findings, coronary CT angiography, and conventional angiography findings in these patients. Results: Of the 39 patients (female/male = 4/35) aged 7-17 years, 66.6% had viral infection in the 2 weeks preceding presentation. Eleven patients were tested for high-sensitivity cardiac troponin I, 28 for high-sensitivity cardiac troponin T, and 10 patients were tested for both biomarkers. The median hs-TnI and hs-TnT values were 6.3 (0.05-29.9) ng/mL and 586 (51-9398) ng/L, respectively. Twenty-three patients showed ST changes on electrocardiography, of whom 11 had ST-elevation in the leads supporting left ventricular involvement. Coronary CT angiography and catheter angiography evaluations performed for differential diagnosis of coronary anomaly and acute coronary syndrome were normal. Cardiac MRI was conducted on 28 patients, and the results in 10 (35.7%) were suggestive of myopericarditis. Conclusions: Myopericarditis is common in the adolescent age group and is generally benign but should be carefully monitored for differential diagnosis and possible complications. Cardiac MRI, which has been used more frequently in recent years, has an important role in differential diagnosis and the follow-up of patients. © The Author(s), 2021. Published by Cambridge University Press.
Keywords: chest pain; Myopericarditis; troponin